Circulating Osteocalcin During Oral Anticoagulant Therapy - Haarlem, L J M van; Knapen, M H J; Hamulyák, K; Vermeer, C (Thrombosis and Haemostasis, 1988)
In this paper we present the following observations:1) In sheep vitamin K-antagonists like phenprocoumon induce a decrease of the serum levels of osteocalcin (bone Gla-protein) and of the affinity of the circulating osteocalcin for hydroxyapatite.2) In sheep vitamin K counteracts the effect of phen-procoumon on the blood coagulation system, but not that on the osteocalcin production.3) In human subjects vitamin K-antagonists also lead to decreased levels of serum osteocalcin and a low affinity of the protein for hydroxyapatite.4) These two variables reached steady-state levels within 24 h after the start of oral anticoagulant treatment and - at continu-ation of the therapy - they remained low for at least several years.
Keywords: Osteocalcin; Vitamin K; Oral anticoagulants; Gammacar; boxyglutamic acid; Blood coagulation; Bone